Pengaruh Digitalisasi Pembelajaran, Kompetensi Profesional dan Komitmen Kerja dimoderasi oleh Budaya Organisasi terhadap Prestasi Siswa pada SMP Negeri 4 Makassar - Misbahuddin, Misbahuddin; Nashriah Akil; Imran Taufik; Ihsan Guntur (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2025)
This study aims to analyze the influence of learning digitalization, teachers' professional competence, and work commitment on student achievement with organizational culture as a moderation variable. This study was conducted at SMP Negeri 4 Makassar by involving a randomly selected sample of students. This study uses a quantitative method with path analysis to test the hypothesis proposed. The results show that the digitization of learning has a significant effect on student achievement, especially when supported by a strong organizational culture. Teachers' professional competence has also been shown to significantly improve student achievement, with influence amplified by a supportive organizational culture. Teachers' work commitment has a significant effect on student achievement, and a positive organizational culture reinforces this influence. These findings emphasize the importance of the role of organizational culture in maximizing the positive influence of learning digitalization, teacher professional competence, and work commitment to student achievement. The recommendations of this study include strengthening organizational culture in schools, improving teachers' professional competence through continuous training, and integrating technology in the learning process to improve overall student achievement.